2015
DOI: 10.1002/adem.201500585
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol‐Assisted Chemical Vapor Deposition of Multi‐Walled Carbon Nanotubes on Steel Substrates for Application in Supercapacitors

Abstract: Carbon nanotubes (CNTs) are grown on to steel substrates by aerosol-assisted chemical vapor deposition using ferrocene in ethanol as the carbon feedstock. The CNTs adopted a highly entangled morphology. Elemental analysis indicates that the main source of carbon for CNT growth is from the cyclopentadiene rings in ferrocene rather than the ethanol solvent. The CNT-coated steel substrates are evaluated for their performance as supercapacitor electrodes. The electrodes exhibit a high geometric capacitance of 3.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The design and infrastructure of AACVD are well-known. 41 A total of 80 mg (0.356 mM) of the precursor palladium(II) acetate, Pd(OAc) 2 , was suspended in methanol (12 mL) and became clear upon the addition of 0.1 mL of trifluoroacetic acid (CF 3 COOH). Afterward, the resultant yellow solution was utilized in AACVD to observe the growth of Pd films.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and infrastructure of AACVD are well-known. 41 A total of 80 mg (0.356 mM) of the precursor palladium(II) acetate, Pd(OAc) 2 , was suspended in methanol (12 mL) and became clear upon the addition of 0.1 mL of trifluoroacetic acid (CF 3 COOH). Afterward, the resultant yellow solution was utilized in AACVD to observe the growth of Pd films.…”
Section: Methodsmentioning
confidence: 99%
“…AACVD was used to grow the palladium thin film electrodes. The design and infrastructure of AACVD are well-known . A total of 80 mg (0.356 mM) of the precursor palladium­(II) acetate, Pd­(OAc) 2 , was suspended in methanol (12 mL) and became clear upon the addition of 0.1 mL of trifluoro­acetic acid (CF 3 COOH).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has shown that steel can act as the catalyst for CNT growth, as it contains elements such as Fe, Co, Ni etc, which are all known to catalyse CNT growth . The ability to grow CNTs on the steel surface eliminates the need of purposely designed expensive catalysts and simplifies the CNT growth significantly compared to the methods reported previously . In terms of low‐cost CNT production at manufacturing scale, this is a key finding as steel is widely available at low‐cost and is robust and stable.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have recently been used in many diverse applications such as sensors, ceramics, filters and membranes, catalysis and energy storage devices,. If the CO 2 and CO from the waste blast furnace gases could be utilized as the carbon source for CNT growth, it will be an economically viable process and a sustainable technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation